Efektivitas Model Problem Based Learning Berbasis Daring terhadap Hasil Belajar IPA Kelas V Sekolah Dasar - Galuh Rizki Amalia; Agustina Tyas Asri Hardini (Peneliti.net, 2020)
The purpose of this research is to determine wether online learning using the problem based learning method is effective to improving learning outcomes of 5'th grade student in Public Elementary School 03 Urutsewu, Ampel District, Boyolali Regency, in year of academic 2019/2020. The subjects of this research were 21 studens of Public Elementary School 03 Urutsewu. This research used the pre-experimental design type “the one-group pretest-posttest” desig. The analyzed data is quantitative data that has been processed using IBM SPSS Statistc 16 software. Data collection uses observation and test. The results of this research were tested using